2016
DOI: 10.1080/01694243.2016.1189869
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bleeding, extra water and superplasticizer on the SCC plastic shrinkage cracking: case of hot weather

Abstract: a laboratory of experimental and numerical Modelling of Materials and structures in civil engineering (laMoMs), university Mouloud Mammeri of Tizi ouzou, Tizi ouzou, algeria; b l2Mgc, cergy-Pontoise university, cergy-Pontoise, france; c laboratory of Materials and durability of constructions (lMdc), university Mentouri of constantine, constantine, algeria ABSTRACT Self-compacting concrete (SCC) is a new material able to be put in place without vibration. However, this advantage is offset by some drawbacks, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In addition, two metal inserts were provided besides the stress riser to accommodate the internal restraints of concrete. Similar test setup was reported in the literature by Boshoff and Combrick, 16 Ghourchian et al, 20 Sirajuddin and Gettu, 28 Leemann et al, 53 Yakoubi et al 54 and in a few more studies. However, based on some investigations it was identified that the provision of these two metal inserts alone was not sufficient to restrain the concrete shrinking 55,56 .…”
Section: Methodssupporting
confidence: 74%
See 4 more Smart Citations
“…In addition, two metal inserts were provided besides the stress riser to accommodate the internal restraints of concrete. Similar test setup was reported in the literature by Boshoff and Combrick, 16 Ghourchian et al, 20 Sirajuddin and Gettu, 28 Leemann et al, 53 Yakoubi et al 54 and in a few more studies. However, based on some investigations it was identified that the provision of these two metal inserts alone was not sufficient to restrain the concrete shrinking 55,56 .…”
Section: Methodssupporting
confidence: 74%
“…In some concrete specimens both primary and secondary cracks were identified after the 24‐hour observation since the exposure to the PSC environment. However, the investigation carried out by Yakoubi et al 54 reports that the PSC development over the time was low. The early age cracking was observed after 1 h for ordinary concrete and after 2 h for self‐compacting concrete, while after half an hour of the time, the modest development of cracks was noticed in the mortars.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations